(untitled) (Publicaciones en Ciencias y Tecnología, 2021)
Currently, semiconductors with magnetic properties represent materials of scientific interest due to their potential applications within the field of spintronics, given the ferromagnetism that they can exhibit at room temperature. In this context, contributing with enlargement of traditional methodologies in the preparation of materials, diluted magnetic semiconductors based on Ni-doped ZnO at 3% and 5% were sintered through of solid reaction method with microwave heating, with the objective of investigating the behavior structural and magnetic of the samples with the dopant percentage. According to the Rietveld refinement of the X-ray diffractograms, the specimens crystallized in wurtzite hexagonal structure, with variations in the lattice parameters caused by the incorporation of Ni in own sites of the Zn. Magnetization measurements as a function of field and temperature revealed the presence of ferromagnetism at room temperature and thermal hysteresis. The FTIR analyzes reflect small changes in the profiles of the absorption bands corresponding to ZnO, a product of the presence of Ni in its network. The results found indicate that the sintering process used, makes it possible to quickly obtain magnetic semiconductors of a nanometric nature with good crystalline quality.